2019
DOI: 10.1080/21663831.2019.1659435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electron–phonon coupling on damage accumulation in molecular dynamics simulations of irradiated nickel

Abstract: The role of the electronic system in high energy displacement cascades is explored. The energy exchange between the electronic and the atomic subsystem is described by the electron-phonon coupling. The electronic effects on the damage accumulation due to 100 keV Ni ion cascades in nickel, a prototype system to a large group of nickel-based high entropy alloys, are investigated for overlapping cascades. It is shown that the energy exchange between the two subsystems affects microstructure evolution, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…From the results presented in Section 3.1 it was evident that traditional MD simulations are not suitable to predict the number, shape, and size of defects induced from the PKA simulations even at low recoil energies, i.e., ∼ 50 keV. This finding is consistent with several other studies where radiation-induced damage has been investigated in SC and NC materials [26,32,[36][37][38]. The difference between MD and MD with electronic effects (including SRIM and 2T-MD) was noticeable in many aspects, including the transient and surviving number of FPs, in the number of defected atoms found in the simulations, and in the dislocation density.…”
Section: Discussionsupporting
confidence: 81%
“…From the results presented in Section 3.1 it was evident that traditional MD simulations are not suitable to predict the number, shape, and size of defects induced from the PKA simulations even at low recoil energies, i.e., ∼ 50 keV. This finding is consistent with several other studies where radiation-induced damage has been investigated in SC and NC materials [26,32,[36][37][38]. The difference between MD and MD with electronic effects (including SRIM and 2T-MD) was noticeable in many aspects, including the transient and surviving number of FPs, in the number of defected atoms found in the simulations, and in the dislocation density.…”
Section: Discussionsupporting
confidence: 81%
“…In other words, the inelastic energy deposited to electrons transfers to the atomic subsystem via el–ph interactions as the electronic subsystem cools down and temperatures are gradually equalized between the two subsystems. Considering the strength of the el–ph interactions and the temperature-dependent energy transfer in CSAs, the 2T-MD simulations , showed that the inelastic energy transfer to the atomic subsystem enhances defect recombination, thus lowering defect production. However, the 2T-MD model is somewhat limited by the quality of the interatomic potentials employed, the description of the electron-temperature dependence of the model parameters, and the use of simple Langevin dynamics for the electron bath.…”
Section: Non-equilibrium Defect Dynamics and Radiation Performancementioning
confidence: 99%
“…Research also suggests that, under certain conditions in some materials, ionization at a desired level can modify preexisting defects or even repair predamage states by promoting recovery processes. , The simulations of coupled electronic and nuclear energy dissipation and subsequent non-equilibrium processes suggest that ballistic recoil events can be facilitated by athermal annealing. Simulations of overlapping high-energy irradiation events suggest that local inelastic thermal spikes can anneal both pre-existing defects and concurrent defects from the ongoing displacement cascades, suppressing damage accumulation. This prediction has been validated with experiments.…”
Section: Non-equilibrium Defect Dynamics and Radiation Performancementioning
confidence: 99%
“…However, MD lacks quantum-mechanical effects required to capture electronic and electron-phonon (e − ph) coupling effects. Even though MD is a classical technique, is it possible to partially incorporate electronic effects within semi-empirical approaches such as the so-called two-temperature model [38][39][40][41][42][43][44][45][46][47][48]. However, these models require several temperature-dependent material parameters that are challenging to compute and, in many cases, remain unavailable.…”
Section: Introductionmentioning
confidence: 99%